Green Synthesis of Reduced Graphene Oxide Nanosheets using Iraqi Rhus coriaria (L.) Fruits Extract and a Study of Its Anticancer Activity - Kadhim, Amenah Salim; Al-Ali, Zainab Shakir Abdullah (Iraqi Journal of Science, 2024)
Ethyl acetate was used to extract bioactive compounds from the fruits of the Iraqi sumac plant Rhus coriaria. This sumac fruit extract was then utilized as a natural reducing agent to convert graphene oxide into reduced graphene oxide (rGO) nanosheets through a green synthesis method. Gas chromatography-mass spectrometry (GC-MS) analysis of the ethyl acetate sumac fruit extract identified phytochemicals that likely facilitated the biosynthesis of the rGO nanosheets. The biosynthesized EERCF-rGO was characterized by using UV-Vis 234 nm. FTIR spectrum was used to know functional groups of EERCF-rGO, XRD spectra of EERCF-rGO displayed sized at 26.91 nm, Raman spectra of EERCF-rGO showed D peak at (1335 cm-1) and a G peak at (1592 cm-1). The morphology of EERCF-rGO was determined using FESEM, which offers plates shape. Also, the TEM of EERCF-rGO showed a size at 12 nm. The biosynthesized of EERCF-rGO appeared to have anticancer activity in vitro cytotoxicity by MTT assay, IC50 is (189.67 μg/mL) against human breast cancer (MCF-7) cell line. The use of biological extracts as reducing agents to produce reduced graphene oxide is an inexpensive, nontoxic, and environmentally friendly approach. The reduced graphene oxide biosynthesized using extracts from the fruits of the Iraqi Rhus coriaria plant demonstrated anticancer properties. This method of green synthesis and the resulting anticancer biomaterial show potential for further development.